MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN KARAKTER WASAKA PADA MUATAN IPAS MENGGUNAKAN MODEL PBL, NHT, DAN INDEX CARD MATCH TERINTEGRASI STEAM PADA SISWA KELAS IV SEKOLAH DASAR - Kamaliah; Annisa, Muhsinah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The problem in this study is the low critical thinking skills and WASAKA character in the IPAS content of fourth grade at Elementary School. The solution to this problem is to use a combination of the Problem-Based Learning, Numbered Heads Together, and Snowball Throwing models integrated with STEAM. The objective of this study is to analyze the critical thinking skills and WASAKA character of students. This study uses Classroom Action Research (CAR) conducted in two cycles. The subjects of this study are 17 students in grade IV at Elementary School. The results of this study indicate that students' critical thinking skills were achieved at a rate of 94% with the criteria of very critical and WASAKA character traits were achieved at a rate of 100% with the criteria of already ingrained.